Effect of sodium carbonate on the rehydration of milk protein isolate powder. (February 2020) - Wu, Shaozong; Fitzpatrick, John; Cronin, Kevin; Miao, Song
Abstract: Milk protein isolate (MPI) powder has poor rehydration ability. An alkaline pH environment has the potential to alter and improve its rehydration behaviour. Sodium carbonate, an approved food additive, is an alkaline reagent and consequently has some potential for improving the rehydration behaviour of MPI powder. The addition of sodium carbonate in this study was adjusted between 0 and 1 g/100 mL concentrations in water. The results showed that wettability worsened with higher sodium carbonate concentrations, due to strong films developing at the powder/water interfaces which inhibited water penetration into the bulk. However, appropriate agitation could effectively wet and disperse the powder. On the other hand, particle size and centrifugal sedimentation studies showed that increasing the sodium carbonate concentration greatly improved the dissolution ability of the MPI powder. The best dissolution occurred in 0.5 g/100 mL sodium carbonate solution, while some large undesirable aggregates occurred at 1 g/100 mL addition. The improved dissolution is most likely due to the higher pH increasing negative electrostatic repulsion and decreasing hydrophobic group attractions on casein micelle surfaces. Graphical abstract: Image 105425 Highlights: Sodium carbonate had a negative effect on powder wettability. Sodium carbonate greatly improved dissolution ability. Best dissolution occurred at around 0.5 g/100 mL sodium carbonate concentration. Improved dissolution was most likely due to alkaline pH.